A Comprehensive Analysis of Strategies to Enhance Business Performance and Shareholder Wealth - Kalsum, Ummu (Advances: Jurnal Ekonomi & Bisnis, 2023)
Through a qualitative literature review, this research investigates strategies to enhance business performance and shareholder wealth. The study explores the role of strategic resource allocation, customer-centric strategies, and adaptation to market dynamics in driving organizational success. A comprehensive synthesis of existing research is conducted, drawing insights from seminal works by scholars such as Barney (1991), Prahalad and Hamel (1990), and Kotler and Keller (2016). Methodologically, the study adopts a qualitative approach to analyze and interpret the findings from the literature. The results highlight the critical importance of integrating organizational resources and capabilities cohesively, prioritizing customer needs, and fostering strategic agility and innovation. Strategic resource allocation emerges as a fundamental determinant of business success, with effective resource allocation enabling firms to sustain competitive advantage and create long-term shareholder value. Customer-centric strategies are key drivers of business growth and profitability, with firms that prioritize customer needs and deliver superior value propositions outperforming competitors. Additionally, adaptation to market dynamics is crucial for organizational resilience and competitiveness, with agile firms better equipped to navigate uncertainty and capitalize on emerging opportunities. Overall, the findings underscore the strategic imperatives for firms to align resources, prioritize customers, and adapt to changing market conditions to enhance business performance and shareholder wealth.